A mosaic form of microphthalmia with linear skin defects - Nina Prepeluh; Bojan Korpar; Andreja Zagorac; Boris Zagradišnik; Andreja Golub; Nadja Kokalj Vokač (BMC, 2018)
Abstract Background Microphthalmia with linear skin defects (MLS) syndrome is a rare neurodevelopmental X-dominant disorder. It presents in females as it is normally lethal in males. Three causative genes for MLS syndrome (OMIM 309801) have been identified all taking part in mitochondrial respiratory chain and oxidative phosphorylation. In our case, we describe a newborn with mosaic deletion encompassing HCCS gene resulting in unilateral microphthalmia and facial skin lesions. Case presentation A girl was born with caesarean section at 40 weeks of gestation. Clinical findings revealed anophthalmia of the left eye. The left eyelids were intact, the orbit was empty and the right eye was normal, without any abnormalities. She had typical linear skin defects on the left cheek, one on the left side of the neck, and two on the 3th and 4th fingers of the left hand. The other clinical findings and the neurological exam were normal. US of the brain and EEG were normal. Molecular karyotyping using BlueGnome CytoChip Oligo 4× 180K array was performed detecting an approximately 18% mosaic 3.3 Mb deletion (arr[GRCh37] Xp22.31p22.2(8,622,553_11,887,361)× 1[0.18]). FISH using RPCI11-768H20 BAC clone on cultivated interphase and metaphase lymphocytes was used to confirm the array results. The observed deletion was present in 29% of cells (46,XX,ish del(p22.2p22.31)(RPCI11-768H20)[60/205]). Conclusions In this report we present a female proband with MLS syndrome. To our knowledge, there have been only few other cases of mosaic MLS syndrome described in the literature. Our case shows that low grade mosaicism does not preclude full clinical presentation and further supports the critical role of the X inactivation pattern in the development of the clinical findings.